2019
DOI: 10.29271/jcpsp.2019.11.1067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Platelet-rich Plasma on Mankin Scoring in Chemically-induced Animal Model of Osteoarthritis

Abstract: Objective: To evaluate the effects of platelet-rich plasma injection on histological changes of osteoarthritis using the modified Mankin score in monoiodoacetate-induced rat knee model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…Cartilage sections were stained with Modified Safranine O-Fast Green FCF Cartilage Stain Kit (Solarbio, Wuhan, China). Two researchers evaluated the stained sections according to the Mankin scoring system 25 without knowing the groups.…”
Section: Methodsmentioning
confidence: 99%
“…Cartilage sections were stained with Modified Safranine O-Fast Green FCF Cartilage Stain Kit (Solarbio, Wuhan, China). Two researchers evaluated the stained sections according to the Mankin scoring system 25 without knowing the groups.…”
Section: Methodsmentioning
confidence: 99%
“…Our sample size was determined by referring to a previous study that examined the modified Mankin score in a mouse MIA OA model. In the study, it was found that a 20% decrease in this histological score after a specific treatment was statistically significant [ 1 ]. Calculations were performed according to this difference with 90% statistical power and α level of 0.05, and it was determined that at least 10 mice were needed for OA flare and OA group in Experiment 1 and, T ( +) and T (-) group in Experiment 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Author details 1 Department of Orthopedic Surgery, Kochi Medical School, Kochi University, 185-1 Oko-cho, Nankoku, Kochi Pref, Japan. 2 Multidisciplinary Pain Center,…”
Section: Fundingmentioning
confidence: 99%
“…The paraffin-embedded samples were sliced into sections with a thickness of 5 μ m. Hematoxylin-eosin (HE) staining and safranin O-fast green staining were used to observe the morphology and proteoglycan loss of the cartilage tissue, respectively. Subsequently, the staining of the cartilage samples was observed by optical microscopy (Olympus Co., Ltd., Tokyo, Japan), and the damage to cartilage tissue was evaluated by the modified Mankin scale ( Table 1 ) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin-eosin (HE) staining and safranin O-fast green staining were used to observe the morphology and proteoglycan loss of the cartilage tissue, respectively. Subsequently, the staining of the cartilage samples was observed by optical microscopy (Olympus Co., Ltd., Tokyo, Japan), and the damage to cartilage tissue was evaluated by the modified Mankin scale (Table 1) [16]. Evidence-Based Complementary and Alternative Medicine nitrogen immediately after removal and then used for the extraction of total protein.…”
Section: Histopathological Examination Of the Cartilagementioning
confidence: 99%